RUI: A Web-based Road Updates Information System using Google Maps API - Grepon, Benzar Glen S.; Margallo, JC P.; Maserin, Jonathan B.; Dompol, Rio Al-Di A. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – Knowing the current situation on every road in an area is still difficult to anticipate. Commuters, riders, and drivers are still dependent on road situations from a local news agency to be well informed and be updated on possible road updates such as vehicular accidents, government road and bridge projects/construction, and other related road obstructions. To give solutions regarding road updates, a web-based roads update information system has been developed that uses Google Maps API allowing people to view and be notified of the real-time updates of the road situation of a specific area. Method - This paper discusses the main system functionalities, including sub-systems and modules of the system, the research approach and methodology, which is the Agile Model, and its impact on disseminating road information and its status. Results – The project has been evaluated using ISO 25010, a quality evaluation system for product/software measuring its functionality, efficiency, reliability, usability, security, maintainability, and portability. Based on the evaluation result, the project has been rated 4.21, signifying an excellent performance based on qualitative description through a Likert scale descriptive interpretation. The project has been running and hosted on the world wide web and is expected to expand its coverage area from its origin country to the rest of the world. Conclusion – Based on the initial findings of the study, the respondents agreed that the developed web system was functional and a massive help to commuters, riders, and people who travel a lot. The system's overall effectiveness and performance were excellent based on the criteria set by ISO/IEC 25010. Recommendations – It is recommended for future development to expand the coverage of the road updates, if possible, including the entire Philippine archipelago for long-drive commuters and drivers to be more updated in terms of road updates. Also, include the use of mobile applications for more user-friendly design and interactions. Research Implications – The study allows viewing and reporting road updates with attachments as proof, informing commuters about what to expect when they travel. The system has been implemented in the municipality of Bukidnon and has been updated now and then for continuous quality improvement. Practical Implications – The main benefit that the Road Updates Information System can do is to inform people who are constantly traveling to be updated on the current situation of a specific road by accessing the system and checking the map on areas to travel and see for themselves the photos and description of a place where road construction, accidents and other causes that delay the traveling time of passengers and travelers. Aside from being informed of the road updates, citizens can also participate by uploading photos and descriptions of what is still going on the roads to the system and be viewed by people who try to access the web portal.